FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA SAAT IPO DI BURSA EFEK INDONESIA - Fachrul A Siregar (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The problem that often arises from IPOs is when there is underpricing, which shows that the actual stock price at the initial time is relatively lower than when traded on the secondary market, therefore examining the factors that affect underpricing at the time of the IPO. The formulation in this study is the occurrence of underpricing, which shows that the actual stock price at the initial time is relatively lower than when traded on the secondary market. The purpose of this study is to analyze Return On Assets, Financial Leverage, Underwriter Reputation, Auditor Reputation, Company Size on Underpricing at the time of Initial Public Offering on the Indonesia Stock Exchange. The type of research used is causal associative research with quantitative research methods with data obtained through Eviews software with a significance level of 5%. The results obtained are Return On Assets, and Underwriter's Reputation have a significant positive effect on underpricing, while Financial Leverage, Auditor's Reputation, and Company Size have a significant negative effect on underpricing. The results of this study also indicate that the activity of strengthening the total assets owned is part of a strategy to reduce the impact of stock underpricing at the time of the IPO.